ANALISIS DAMPAK FINANCIAL DISTRESS TERHADAP HUBUNGAN ANTARA PENGUNGKAPAN LAPORAN KEBERLANJUTAN DAN KONSERVATISME - Hanan Octiana (2020)
This research is a quantitative study that aims to determine the influence of the impact of financial distress moderate relationship between sustainability reports on conservatism. This research uses a manufacturing company sub sector Good Consumer Industry as a sample. The sample selection uses non-probability sampling after determining the number of acceptable samples, which is 40 companies out of 58 companies. Testing the hypothesis in this study using Multiple Linear Regression analysis with the STATA 13 program and a significance level of 5% (0.05). The results of examination are obtained (1) there is no significant effect of sustainability reports on conservatism, (2) there is no effect of financial distress moderating the relationship between sustainability reports and conservatism.